Application of alternative synthetic kernel approximation to radiative transfer in regular and irregular two-dimensional media. (January 2017) - Altaç, Zekeriya; Sert, Zerrin
Abstract: Alternative synthetic kernel ( ASK N ) approximation, just as the standard SK N method, is derived from the radiative integral transfer equations in full 3D generality. The direct and diffuse terms of thermal radiation appear explicitly in the radiative integral transfer equations as surface and volume integrals, respectively. In standard SK N method, the approximation is employed to the diffuse terms while direct terms are evaluated analytically. The alternative formulation differs from the standard one in that the direct radiation wall contributions are also approximated with the same spirit of the synthetic kernel approximation. This alternative formulation also yields a set of coupled partial differential-the ASK N –equations which could be solved using finite volume methods. This approximation is applied to radiative transfer calculations in regular and irregular two-dimensional absorbing, emitting and isotropically scattering media. Four benchmark problems-one rectangular and three irregular media-are considered, and the net radiative flux and/or incident energy solutions along the boundaries are compared with available exact, standard discrete ordinates S4 and S12, modified discrete ordinates S4, Monte Carlo and collocation spectral method to assess the accuracy of the method. The ASK N approximation yields ray effect free incident energy and radiative flux distributions, and low order ASK N solutions are generally better than those of the high order standard discrete ordinates method. Highlights: Alternative Synthetic Kernel approximation is proposed. The method is tested for regular and irregular participating media. The method is compared with exact, DOM, Monte Carlo and collocation methods. The results are comparable to DOM.